Modern Philosophy - A Comparison Of History - Qiyam Nazarov (Peerian Journals Publishing, 2024)
It is known that the spheres of spiritual life and the events that take place in them are interrelated, which is one of the important laws of this sphere. In this regard, in the current period of Uzbekistan's development, the attitude towards the heritage of our ancestors is rising to a new level. On the contrary, the fact that in recent years the attention to the field of spirituality has increased tremendously and it has become an important direction of state policy, the fact that a new activity system has been formed in this regard indicates that this process is expanding and strengthening
Keywords: Philosophy; expanding; attention; contrary